2010
DOI: 10.1183/09031936.00068810
|View full text |Cite
|
Sign up to set email alerts
|

Agenesis of paranasal sinuses and nasal nitric oxide in primary ciliary dyskinesia

Abstract: Agenesis of paranasal sinuses has only been described in case reports of patients with primary ciliary dyskinesia (PCD). As agenesis of paranasal sinuses may contribute to low nasal nitric oxide levels, a common finding in PCD, we speculated that this condition might frequently occur in PCD patients.Patients referred for PCD evaluation were consecutively recruited for 30 months. In addition to standard diagnostic testing for PCD, a computed tomography (CT) scan of paranasal sinuses was performed in all subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 32 publications
2
72
1
1
Order By: Relevance
“…Contrary to the majority of published data [3,7,47,48,52,54], two groups [53,58] have recently reported normal and raised levels of nasal nitric oxide in patients with PCD. A study of PCD-positive patients, confirmed by live ciliary function analysis and scrutiny of ciliary axonemal ultrastructure [6], reported five patients with nasal nitric oxide within or above the normal range [53].…”
Section: Screening: the Role Of Nasal Nitric Oxidementioning
confidence: 43%
See 3 more Smart Citations
“…Contrary to the majority of published data [3,7,47,48,52,54], two groups [53,58] have recently reported normal and raised levels of nasal nitric oxide in patients with PCD. A study of PCD-positive patients, confirmed by live ciliary function analysis and scrutiny of ciliary axonemal ultrastructure [6], reported five patients with nasal nitric oxide within or above the normal range [53].…”
Section: Screening: the Role Of Nasal Nitric Oxidementioning
confidence: 43%
“…A study of PCD-positive patients, confirmed by live ciliary function analysis and scrutiny of ciliary axonemal ultrastructure [6], reported five patients with nasal nitric oxide within or above the normal range [53]. A further study demonstrated that 24% of patients at an Italian PCD clinic (n541) had nasal nitric oxide of .250 ppb, although the diagnostic evidence for PCD in these patients is unclear [58]. These studies highlight that patients with a history strongly suggestive of PCD should not be excluded from further diagnostic evaluation on the basis of nasal nitric oxide.…”
Section: Screening: the Role Of Nasal Nitric Oxidementioning
confidence: 99%
See 2 more Smart Citations
“…A few groups have recently reported normal levels of nasal NO in a minority of patients with PCD (1,11,13). These studies highlight that patients with a history strongly suggestive of PCD should not be excluded from further diagnostic evaluation on the basis of nNO, and also that, while providing an excellent screening test, nNO is not diagnostic and low levels should trigger referral to a highly specialized diagnostic center.…”
Section: Nasal Nitric Oxide Is An Important Test In the Diagnostic Pamentioning
confidence: 99%